Peningkatan Kapasitas Kader Dalam Pencegahan DBD Di Desa Jagabaya, Kecamatan Warunggunung Kabupaten Lebak Banten - Agus Riyanto; Endang Uji Wahyuni; Bina Rachma Permatasari; Rojali (CV. Multi Kreasi Media, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection. DHF is an acute disease with clinical manifestations of bleeding that causes shock, which can lead to death. One of the areas affected by the DHF virus is Lebak Regency, Banten, with 1,400 people infected with the DHF virus and 6 deaths over a period of 4 months. This is due to weather changes and the community's lack of concern for the environment, allowing water to stagnate and breed Aedes aegypti mosquitoes. Of the 12 subdistricts endemic to dengue fever in Lebak Regency, there are four urban areas that are endemic to dengue fever, namely Rangkasbitung, Cibadak, Kalanganyar, and Warunggunung subdistricts. This is due to the high population density in these areas. As of 2024, the Lebak Health Office (Dinkes) has recorded 1,327 cases of dengue fever in Lebak Regency, with 6 deaths. This number of dengue fever cases has increased compared to 2023, which reached 760 cases and four deaths. During this community service activity, the Jagabaya Village area in the subdistrict will receive guidance from the Jakarta II Ministry of Health Polytechnic in collaboration with the Community Health Center to RW/RT cadres so that the community can independently control and reduce the incidence of dengue fever by learning how to eliminate breeding sites and use ovitraps. This initiative will be ongoing, and its outcomes will be evaluated, potentially serving as a model for other regions in implementing vector-borne disease control measures.